How do Basel IV regulation announcements impact market performance of European banks? - Pereira, Maria Inês Coelho (2018)
This dissertation examines final Basel III reforms announcements by the BCBS and assesses their impact on market performance of European banks using event study methodology. Following this initial part of the analysis, regression analyses are performed using explanatory variables referring to bank features such as liquidity, capitalisation, profitability and size. Country controls are also employed to analyse possible different countries reactions. Basel IV (final Basel III rules) announcements generally reflect a favourable response by the banks comprised in the sample, against initial expectation. This represents an aggregate shareholder wealth gain of over €40 million for statistically significant events, around a 4% increase against normal performance. This research shows that while bank-specific variables are not generally meaningful explaining variation in market valuation of European banks, the discrepancy between countries offers more insightful findings. GIIPS countries and sovereigns whose banks use their own IRB models may show possible vulnerabilities, yet do not seem to be lagging behind their European peers. Observed results may reveal that risk management policies and compliance have become more harmonised and aligned. This study’s findings may then provide evidence that Basel IV is an important step in reducing uncertainty, so as to reassure reliability in financial institutions and a safer banking environment in the EU.